Dowództwo Okręgu Generalnego „Lwów”, czyli o początkach terenowej administracji wojskowej w Małopolsce Wschodniej (1919-1921) - OSTANEK , Adam (Historia i Świat, 2014)
The structure of the present work is based both on chronology and theme. The main research problem of the article is to establish the facts about the functioning of the administrative apparatus of the Polish Army in the General District “Lvov”. All of the elements related to the organizational structure of the District Command are discussed . Additionally, the author attempts to reconstruct the data concerning the personal depart-ment of the district’s management. Between 1919-1921 the General District “Lvov” was one of several (?) military units in Poland. The administration of the subject area, which covered 37,400 square km, belonged to the commander located in Lvov. According to the public list from 1921 almost 3,5 mln people lived within this military dis-trict’s borders. For the whole discussed period the General District Command “Lvov” was the main war institution in East Lesser Poland (Małopolska). Although the succes-sive commanders standing on the district’s head had different prerogatives and competence, in general, they controlled material, money and tax economy of these formations and were concerned with discipline and order. The essential aim of the district’s commander was the constant coop-eration with both representatives of the authorities and the local people.